A Study Of In-Situ L-Connections For Precast Concrete Sandwich Panel Building System - Pang, Siaw Chin (2002)
A number of fifty four specimens have been tested in order to investigate the strength and behaviour of cast-in-situ right angle vertical connections between two precast concrete sandwich panels (PCSP) under pure moment and shearing force separately. Four types of connections have been chosen for study, namely connection types A, B C and D, defined by the length of the anchor steel bars in the connection area, being respectively 105mm, 190mm, 2 85mm and 2 89mm. Three different spacings of ASB in the connections, viz. 100mm, 200mm and 300mm have been attempted for each connection type. For both pure moment and shearing force tests, the forces are increased gradually till the specimens fail. In the pure moment tests, the deformations of the specimens including the change of the included angle, the concrete surface strains and the strains in the anchor steel bar have been recorded, whereas for the shearing force tests, only the shear displacements of the specimens have been recorded. Structural behaviour of the connections in flexure has been observed for each type of connection in regards to its strength, ductility and rigidity. Connection type D is found, amongst the four types studied, to have the highest strength and ductility.